Pemberdayaan dan Pelatihan kepada Masyarakat Peduli Sanitasi Total Berbasis Masyarakat (STBM) Pilar Pertama - Sumihardi; Novelasari; Darwel (Jurnal Pengabdian Masyarakat Cendikia Jenius, 2025)
The village of IV Koto Mudiek, Batang Kapas District, has 1,891 households (KK) with access to proper toilets, while 310 households (KK) still use inadequate toilets. Meanwhile, surveys/observations show that many people still defecate inappropriately, especially in rivers. One effort is the community's involvement in Community-Based Total Sanitation (STBM) with the first pillar. The aim of this community service is to achieve a change in the community's behavior and to commit to stopping open defecation, especially in the river. The method of this service is carried out through empowerment and training for the community (participants) through lectures, discussions, and simulations with material on the 5 STBM Pillars, with a specific focus on the First Pillar of STBM, which is Stop Open Defecation. The results of the pretest and posttest showed an improvement in the participants' understanding of the 5 STBM pillars, particularly the first pillar, Stop Open Defecation. Additionally, the commitment/agreement of participants to encourage people who still defecate in the river to use proper toilets was achieved. Furthermore, they agreed not to throw trash into the river. The program in Kenagarian IV Koto Mudiek improved STBM understanding, commitment to stop open defecation, and protect rivers.